Desarrollo de una aplicación Web de gestión y control del historial clínico en el departamento médico de la ESPAM MFL - Alvarado Napa, Diego Armando (2018)
The realization of this work was carried out with the aim of developing a web application that manages and controls the clinical history to optimize the care of patients at the ESPAM MFL medical department. The SCRUM Methodology that provides the necessary guidelines for the development of web applications was applied, this has three phases, in the first the general requirements of the software were defined, in the second the application was developed taking into account the previous requirements and the third phase concluded with the total revision of the functionality of the system. To establish the functional requirements of the system, the IEEE 830 standard was used to standardize and certify the set of requirements for the development of the application, and use case diagrams with unified modeling language (UML) were designed to define the functional structure of the system from the user's point of view. The main tools used for the development of the web application were: the integrated development environment (IDE) of Visual Studio 2015 programming, the software architecture pattern (MVC), the Razor view engine with HTML5 and CSS3, in addition to the C#, JavaScript and XML languages. Through this work, the total integration of the processes in the medical department and the systematized control of compliance with them were obtained.